Harmonisation of life cycle assessment practices in horizon Europe battery technology projects - Sara M. Pinto; Maria Soares; Emanuel J. Lourenço; Emanuel Glans; Mats Zackrisson; Kristin Fransson; Gemma Mendoza; Guillermo Ormazabal; Cristina Cerrillo; Abdur-Rahman Ali; Maeva Lavigne Philippot (Environmental Impact Assessment Review, 2026)

Mechanistic insights into combined effect of magnetic field and transglutaminase on the modification of peanut oleosomes-filled myofibrillar protein emulsion gels - Muhammad Hamza Sardar; Maria Rahman; Taskeen Zafar; Chaoyi Duan; Mingfeng Xu; Sida Fu; Rongrong Yu (Innovative Food Science & Emerging Technologies, 2026)

Effect-based methods and effect-based trigger values for estrogenicity monitoring in surface water: an interlaboratory study - Livia Gómez; Dimitar Marinov; Elena Porcel-Rodríguez; Diletta Scaccabarozzi; Isabella Sanseverino; Pietro Sciuto; Frank Narendja; Romana Hornek-Gausterer; Katharina Lenz; Carole Chalon; Yves Marneffe; Přemysl Soldán; et al. (Environmental Research, 2026)

Effectiveness of soil remediation intervention of abandoned used lead-acid battery recycling sites to reduce lead exposure among children: A three-arm pretest-posttest non-equivalent comparison group trial - Mahbubur Rahman; Jesmin Sultana; Supta Sarker; Shaikh Sharif Hasan; Sarker Masud Parvez; Mitali Das; Gordon K. Binkhorst; Jenna E. Forsyth; Peter J. Winch; Rubhana Raqib; Stephen P. Luby; Maria Kippler; et al. (International Journal of Hygiene and Environmental Health, 2026)

Effects of ultrasound-assisted emulsification and enzyme-catalyzed cross-linking on the structural, rheological and digestive properties of myofibrillar protein-peanut oleosome emulsion gels - Maria Rahman; Ruixi Li; Shahzad Farooq; Mingfeng Xu; Sida Fu; Rongrong Yu (Food Hydrocolloids, 2026)

Photocatalytic removal of textile dyes: Analytical strategies for post-degradation evaluation - Md. Khalid Hossain Shishir; Md. Shoyeb Akand; Mohshin Maola; Maria Ferdusi Monira; Md. Rifat; Nafis Rahman Sayeem; Al Masud; Sukanta Mondal; Gazi Md. Arifuzzaman Khan (Desalination, 2026)

Tailoring chickpea protein functionality for food applications through supercritical CO2 processing - Gomathy Sandhya Subramanian; Daryl Lee; Su Hui Lim; Sergey Gorelik; Celyne Halim; Ashley Lim; Shi Jie Ang; Dylan Hao Wen Swee; Uma Jingxin Tay; Sreenivasa Reddy Puniredd; Khin Yin Win; Yoganathan Kanagasundaram; et al. (Food Research International, 2025)

Chronic arsenic exposure and cardiometabolic biomarkers in adolescents in the MINIMat longitudinal study - Evana Akhtar; Anjan Kumar Roy; Md. Ahsanul Haq; Md. Jakarea; Anjuman Ara; Aliya Naheed; Md. Anisur Rahman; Ondine S. von Ehrenstein; Maria Kippler; Yukiko Wagatsuma; Rubhana Raqib (Journal of Trace Elements in Medicine and Biology, 2025)

Childhood exposure to polycyclic aromatic hydrocarbons (PAHs) and cardiometabolic indicators in childhood and adolescence: findings from a cohort study in rural Bangladesh - Mercedes Trask; Syed Moshfiqur Rahman; Mariza Kampouri; Rubhana Raqib; Eva-Charlotte Ekström; Eero Kajantie; Mohammad Redwanul Islam; Annette M. Krais; Christian Lindh; Anisur Rahman; Maria Kippler (Environmental Research, 2025)

Impacts of N-(n-Butyl)thiophosphoric triamide (NBPT) on the physicochemical properties of milk protein isolate (MPI) dispersions: A study on micelle integrity - Maria P. Byrne; Patrick J. Forrestal; Tom F. O’ Callaghan; Niharika Rahman; Aishwarya Ray; Martin Danaher; Bernard M. Corrigan; Noel A. McCarthy; Chikere G. Nkwonta; Karl Richards; Farhad Garavand; Enda Cummins; et al. (Food Structure, 2025)

Enhancing Efavirenz Bioavailability Via Polymer-Based Buccal Administration: Optimization and Characterization of Nanocrystal-Loaded Dissolving Microneedle Delivery Systems - Khairiyah Khairiyah; Muh. Bisfain Asaf; Nur Afni Annisa Achmad; Rachmatya W. Tuna; Irfan Kurniawan; Anugerah Yaumil Ramadhani Aziz; Maria Mir; Juan Domínguez-Robles; Mónica Millán-Jiménez; Ilyas Essadki-Aittaji; Ana B. Cobo-González; Muhammad Aswad; et al. (The AAPS Journal, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Avocado ( Persea americana Mill) and its phytoconstituents: potential for cancer prevention and intervention - Taylor E. Collignon; Kassidy Webber; Josh Piasecki; Austin S. W. Rahman; Arijit Mondal; Sandra Maria Barbalho; Anupam Bishayee (Critical Reviews in Food Science and Nutrition, 2024)

Computational antigenic insights into the novel NADC-34-like Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) isolate YC-2020 - Maria Karolaynne da Silva; Jonas Galileu Ferreira de Aquino; Claudio Bruno Silva de Oliveira; João Firmino Rodrigues-Neto; Miadur Rahman; Shahina Akter; Umberto Laino Fulco; Yousef A. Bin Jardan; Samir Ibenmoussa; Jonas Ivan Nobre Oliveira (Veterinary Immunology and Immunopathology, 2024)

Drivers of habitat availability for terrestrial mammals: Unravelling the role of livestock, land conversion and intrinsic traits in the past 50 years - Michela Pacifici; Andrea Cristiano; Maria Lumbierres; Mauro Lucherini; David Mallon; Erik Meijaard; Sergio Solari; Marcelo F. Tognelli; Jerrold L. Belant; Thomas M. Butynski; Drew Cronin; Jean‐Pierre d'Huart; et al. (Global Change Biology, 2023)
The global decline of terrestrial species is largely due to the degradation, loss and fragmentation of their habitats. The conversion of natural ecosystems for cropland, rangeland, forest products and human infrastructure are the primary causes of habitat deterioration. Due to the paucity of data on the past distribution of species and the scarcity of fine‐scale habitat conversion maps, however, accurate assessment of the recent effects of habitat degradation, loss and fragmentation on the range of mammals has been near impossible. We aim to assess the proportions of available habitat within the lost and retained parts of mammals' distribution ranges, and to identify the drivers of habitat availability. We produced distribution maps for 475 terrestrial mammals for the range they occupied 50 years ago and compared them to current range maps. We then calculated the differences in the percentage of ‘area of habitat’ (habitat available to a species within its range) between the lost and retained range areas. Finally, we ran generalized linear mixed models to identify which variables were more influential in determining habitat availability in the lost and retained parts of the distribution ranges. We found that 59% of species had a lower proportion of available habitat in the lost range compared to the retained range, thus hypothesizing that habitat loss could have contributed to range declines. The most important factors negatively affecting habitat availability were the conversion of land to rangeland and high density of livestock. Significant intrinsic traits were those related to reproductive timing and output, habitat breadth and medium body size. Our findings emphasize the importance of implementing conservation strategies to mitigate the impacts caused by human activities on the habitats of mammals, and offer evidence indicating which species have the potential to reoccupy portions of their former range if other threats cease to occur.

Measurement of grass uptake of the urease inhibitor NBPT and of the nitrification inhibitor dicyandiamide co-applied with granular urea - Niharika Rahman; Chikere G Nkwonta; Martin Danaher; Karl G. Richards; Sean A Hogan; Enda Cummins; Macdara O’ Neill; Aishwarya Ray; Maria P. Byrne; Patrick J. Forrestal (Environmental Science and Pollution Research, 2023)

Polycyclic aromatic hydrocarbon (PAH) exposure during pregnancy and child anthropometry from birth to 10 years of age: Sex-specific evidence from a cohort study in rural Bangladesh - Syed Moshfiqur Rahman; Annachiara Malin Igra; Julie Y. Essig; Eva-Charlotte Ekström; Kristian Dreij; Mercedes Trask; Christian Lindh; Shams El Arifeen; Anisur Rahman; Annette M. Krais; Maria Kippler (Environmental Research, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

First assessment of microplastics in offshore sediments along the Lebanese coast, South-Eastern Mediterranean - Mahfouz Celine; Jemaa Sharif; Kazour Maria; Hassoun Abed El Rahman; Lteif Myriam; Ghsoub Myriam; Ouba Anthony; Amara Rachid; Fakhri Milad (Marine Pollution Bulletin, 2023)

Placenta is Capable of Protecting the Male Fetus from Exposure to Environmental Bisphenol A - Monika Lukasiewicz; Jan Czerniecki; Donata Ponikwicka-Tyszko; Maria Sztachelska; Marta Hryniewicka; Edyta Nalewajko-Sieliwoniuk; Wieslaw Wiczkowski; Beata Banaszewska; Robert Milewski; Jorma Toppari; Ilpo Huhtaniemi; Nafis A. Rahman; et al. (Exposure and Health, 2021)
Embryo–fetal exposure to bisphenol A (BPA) could be related to poor male reproductive parameters in rodents, but this concept has not been convincingly confirmed in humans. We investigated the association of environmental BPA exposure of pregnant women with selected endocrine and anthropometric parameters of male newborns. We analyzed plasma BPA from pregnant mothers, umbilical cord, and placental tissues ( n = 117/each group) by liquid chromatography and mass spectrometry. LH, FSH, AMH, TGFβ2, inhibin B, and selected sex steroids were measured in cord plasma. The infant anthropometric parameters included anogenital distance, stretched penile length, head circumference, birthweight, and length. The median BPA concentrations in maternal and umbilical cord plasma, and in placental tissue were 19.0, 8.0, and 22.2 nmol/L, respectively, the levels thus being over twofold lower in the fetal circulation than in the mother or placenta. The BPA concentrations measured were 100–1000-fold lower than those demonstrated in animal experiments to have endocrine disrupting effects. Multivariable regression analysis indicated no significant correlations between the maternal/fetal/placental BPA concentrations and any of the hormone levels or anthropometric parameter measured. Plasma concentrations of BPA confirmed both maternal, placenta, and fetal exposure to environmental BPA, but the concentrations were orders of magnitude lower than those with documented endocrine disrupting activity. Moreover, the maternal/fetal concentration gradient as well as the lack of correlations of BPA levels with any major endocrine or anthropometric parameters measured in the newborns suggest a protective role for the placenta in reducing fetal exposure to the environmental BPA.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Field Survey and Numerical Modelling of the December 22, 2018 Anak Krakatau Tsunami - Jose C. Borrero; Tubagus Solihuddin; Hermann M. Fritz; Patrick J. Lynett; Gegar S. Prasetya; Vassilios Skanavis; Semeidi Husrin; Kushendratno; Widjo Kongko; Dinar C. Istiyanto; August Daulat; Dini Purbani; et al. (Pure and Applied Geophysics, 2020)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Correction to: The CAPOS mutation in ATP1A3 alters Na/K-ATPase function and results in auditory neuropathy which has implications for management - Lisbeth Tranebjærg; Nicola Strenzke; Sture Lindholm; Nanna D. Rendtorff; Hanne Poulsen; Himanshu Khandelia; Wojciech Kopec; Troels J. Brünnich Lyngbye; Christian Hamel; Cecile Delettre; Beatrice Bocquet; Michael Bille; et al. (Human Genetics, 2018)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

The CAPOS mutation in ATP1A3 alters Na/K-ATPase function and results in auditory neuropathy which has implications for management - Lisbeth Tranebjærg; Nicola Strenzke; Sture Lindholm; Nanna D. Rendtorff; Hanne Poulsen; Himanshu Khandelia; Wojciech Kopec; Troels J. Brünnich Lyngbye; Christian Hamel; Cecile Delettre; Beatrice Bocquet; Michael Bille; et al. (Human Genetics, 2018)

The seed endosphere of Anadenanthera colubrina is inhabited by a complex microbiota, including Methylobacteriumspp. and Staphylococcus spp. with potential plant-growth promoting activities - Pasquale Alibrandi; Massimiliano Cardinale; MD Mahafizur Rahman; Francesco Strati; Paolo Ciná; Marta L. de Viana; Eugenia M. Giamminola; Giuseppe Gallo; Sylvia Schnell; Carlotta De Filippo; Mirella Ciaccio; Anna Maria Puglia (Plant and Soil, 2018)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

An oral cancer biobank initiative: a platform for multidisciplinary research in a developing country - Rosnah Binti Zain; Vimmitra Athirajan; Wan Maria Nabillah Ghani; Ishak Abdul Razak; Raja Jalaludin Raja Latifah; Siti Mazlipah Ismail; Atiya Abdul Sallam; Anita Zarina Bustam; Zainal Ariff Abdul Rahman; Adam Hussien; Norain Talib; Sok Ching Cheong; et al. (Cell and Tissue Banking, 2013)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)